Fault Analysis System for High Speed EMU Control Network Based on Fault Tree - XU Qing; LI Chuanyu (Kongzhi Yu Xinxi Jishu)
At present, fault analysis of high speed EMU is to classify and list all the fault causes according to the working principle, characteristics, functions and structure of the system. Once a fault occurs, it checks and eliminates fault causes one by one according to the established procedures. The analysis steps of this method are relatively fixed, and cannot accurately reflect the relationship between the faults at different levels of the system. This paper proposes a fault analysis method for the network control system of high speed EMU based on fault trees. That is, on the basis of analyzing the fault conditions, a corresponding fault tree model is established, all the direct causes of the listed intermediate events are found out through logical reasoning, and a deductive method is adopted to continuously extend and excavate in order to quickly determine the optimal procedure for failure analysis. As to realize more convenient viewing, browsing and analysis of fault database, based on the method of fault tree, this paper combines VB programming and Access database software to design a fault tree based high speed EMU network fault analysis system to assist technicians in quickly analyzing faults. As an example of pantograph malfunction, through the application of the high speed EMU network fault analysis system, it can be seen that the system can simplify the fault diagnosis process, quickly locate the fault, obtain fault diagnosis suggestions, and shorten the fault analysis time by more than 0.5 h.